Cytomegalovirus infection does not impact on survival or time to first treatment in patients with chronic lymphocytic leukemia. Issue 8 (1st June 2016) - Parry, Helen Marie; Damery, Sarah; Hudson, Christopher; Maurer, Matthew J.; Cerhan, James R.; Pachnio, Annette; Begum, Jusnara; Slager, Susan L.; Fegan, Christopher; Man, Stephen; Pepper, Christopher; Shanafelt, Tait D.; et al.
Abstract : Human cytomegalovirus (HCMV) is a widely prevalent herpes virus which establishes a state of chronic infection. The establishment of CMV‐specific immunity controls viral reactivation and leads to the accumulation of very large numbers of virus‐specific T cells which come to dominate the immune repertoire. There is concern that this may reduce the immune response to heterologous infections and HCMV infection has been associated with reduced survival in elderly people. Patients with chronic lymphocytic leukemia (B‐CLL) suffer from a state of immune suppression but have a paradoxical increase in the magnitude of the CMV‐specific T cell and humoral immune response. As such, there is now considerable interest in how CMV infection impacts on the clinical outcome of patients with B‐CLL. Utilizing a large prospective cohort of patients with B‐CLL ( n  = 347) we evaluated the relationship between HCMV seropositivity and patient outcome. HCMV seropositive patients had significantly worse overall survival than HCMV negative patients in univariate analysis (HR = 2.28, 95% CI: 1.34–3.88; P  = 0.002). However, CMV seropositive patients were 4 years older than seronegative donors and this survival difference was lost in multivariate modeling adjusted for age and other validated prognostic markers ( P  = 0.34). No significant difference was found in multivariate modeling between HCMV positive and negative patients in relation to the time to first treatment (HR = 1.12, 95% CI: 0.68–1.84; P  = 0.65). These findings in a second independent cohort of 236 B‐CLL patients were validated. In conclusion no evidence that HCMV impacts on the clinical outcome of patients with B‐CLL was found. Am. J. Hematol. 91:776–781, 2016. © 2016 Wiley Periodicals, Inc.